Buried histories : the anticommunist massacres of 1965-1966 in Indonesia - Roosa, John (Critical human rights., 2020)
"In 1965-66, army-organized massacres claimed the lives of hundreds of thousands of supporters of the Communist Party of Indonesia. Very few of these atrocities have been studied in any detail, and answers to basic questions remain unclear. What was the relationship between the army and civilian militias? How could the perpetrators come to view unarmed individuals as dangerous enemies of the nation? Why did Communist Party supporters, who numbered in the millions, not resist? Drawing upon years of research and interviews with survivors, Buried Histories is an impressive contribution to the literature on genocide and mass atrocity, crucially addressing the topics of media, military organization, economic interests, and resistance."--Publisher description